Penerapan Web Scraping Sebagai Media Pencarian dan Menyimpan Artikel Ilmiah Secara Otomatis Berdasarkan Keyword - Flores, Veronica Ambassador; Permatasari, Putri Agung; Jasa, Lie (Majalah Ilmiah Teknologi Elektro; Vol 19 No 2 (2020): (Juli - Desember) Majalah Ilmiah Teknologi ElektroDO - 10.24843/MITE.2020.v19i02.P06, 2020)
A scientific article is a reference that is usually used by a student or researcher to make a study. Scientific articles can be searched freely on the Internet, but the search process is often time-consuming due to the large number of scientific articles on the Internet. This search can be done automatically by utilizing the Web Scraping Technique as a data collection technique on a website on the Internet. Depth First Search (DFS) method is a search method that can be used to do web Scraping on the Internet. This system works by processing Keywords in the form of Keywords from the topic of scientific articles to be searched for given by the user. Then the system will send a request to the server to look for links related to these Keywords. After the search results have been found, the system will automatically download and save the article format .pdf to the user's computer. The results of this study indicate that 134 articles that were successfully downloaded using this system show that this system can work very well to search for scientific articles with a level of relevance between the articles searched for articles downloaded by 99%.